Board Characteristics and Firm Performance: Evidence from Bursa Malaysia Ace Market - Nabihah, Aminaddin (2013)
Corporate board is one of the most important corporate governance mechanisms that monitor and advise management in carrying responsibilities to protect shareholder interests. However, the relationship between board of directors and firm performance was still much debated. This study was carried out in order to seek the relationship between board characteristics and firm performance in companies listed on ACE Market at Bursa Malaysia. The data for a year; 2011 for 89 companies was collected from the annual report and the Data Stream. The dependent variables were Tobin’s q and return on assets (ROA) while the independent variables were board size, CEO ownership, independent directors, firm size, and firm age. The result of multiple regression model and correlation showed that board size has a negative relationship with Tobin’s Q but a positive relationship with the ROA. CEO ownership shows a negative relationship with Tobin’s Q and positive relationship with ROA. Director independence has negative relationships with both Tobin’s Q and ROA. Results for the firm size show a negative relationship with Tobin’s Q and a positive one with ROA while firm age indicate positive relationships for both Tobin’s Q and ROA. Of the independent variables, only firm size has a significant relationship with both Tobin’s Q and ROA while CEO ownership shows a significant relationship with ROA.